SURVIVAL OF LUNG CANCER PATIENTS RESIDING IN TOMSK REGION (2004–2013) - E. L. Choynzonov; L. D. Zhuikova; A. O. Ananina; T. V. Polishchuk; L. V. Pikalova (Сибирский онкологический журнал)
A 10-year survival of 3482 lung cancer patients residing in Tomsk region was studied. Based on the populationbased cancer registry data, the observed, corrected and relative survival rates were calculated by the actuarial method taking into consideration age, sex, disease stage and place of residence of the patients. Survival rates were lower in males than in females: the difference in the overall observed survival (OS) rate was from 5.1 % (8-year OS) to 7.3 % (2-year OS). An inverse relationship between survival and cancer spread was observed. Survival rates were higher for urban populations than for rural populations. The analysis indicated that most lung cancer cases were diagnosed at an advanced stage. Survival rates demonstrated relatively equal levels of cancer care in different regions of Russia. When comparing survival rates in Tomsk region with those in Europe and the USA, it was shown that one-year survival was lower in Tomsk region than in Europe and the USA, thus indicating more effective cancer screening programs in European countries and the USA.